Silicone rubber membrane devices permit islet culture at high density without adverse effects - Avgoustiniatos, Efstathios S.; Mueller, Kate R.; Scott III, William E.; Kitzmann, Jennifer P.; Suszynski, Thomas M.; Perrault, Brian E.; Falde, Eric J.; Balamurugan, A. N.; Hering, Bernhard J.; Putnam, Charles W.; Papas, Klearchos K. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Conventional culture conditions, such as in T-flasks, require that oxygen diffuse through the medium to reach the islets; in turn, islet surface area density is limited by oxygen availability. To culture a typical clinical islet preparation may require more than 20 T-175 flasks at the standard surface area density of 200 IE/cm 2 . To circumvent this logistical constraint, we tested islets cultured on top of silicon gas-permeable (GP) membranes which place islets in close proximity to ambient oxygen.Methods: Oxygenation of individual islets under three culture conditions, standard low-density, non-GP high density, and GP high density, were first modeled with finite element simulations. Porcine islets from 30 preparations were cultured for two days in devices with GP membrane bottoms or in paired cultures under conventional conditions. Islets were seeded at high density (HD, ~4000 IE/cm 2 , as measured by DNA) in both GP and non-GP devices.In simulations, individual islets under standard culture conditions and high density cultures on GP membranes were both well oxygenated whereas non-GP cultured islets were anoxic. Similarly, compared to the non-GP paired controls, islet viability and recovery were significantly increased in HD GP cultures. The diabetes reversal rate in nude diabetic mice was similar for HD GP devices and standard cultures but was minimal with non-GP HD cultures.Culturing islets in GP devices allows for a 20-fold increase of islet surface area density, greatly simplifying the culture process while maintaining islet viability and metabolism.